Strain effects on the work function of an organic semiconductor - Yanfei Wu (Nature Portfolio, 2016)
The understanding of strain effect on electronic properties of organic semiconductors is crucial for the designs of flexible electronics. Here, Wu et al.characterize the tensile and compressive strain effects on the work function of rubrene single crystals as a benchmark system.